Validation and meaningful within-patient change in work productivity and activity impairment questionnaire (WPAI) for episodic or chronic migraine - Janet H. Ford; Wenyu Ye; David W. Ayer; Xiaojuan Mi; Swati Bhandari; Dawn C. Buse; Richard B. Lipton (SpringerOpen, 2023)
Abstract Background No available studies demonstrate validity and meaningful change thresholds of Work Productivity and Activity Impairment (WPAI) questionnaire in patients with migraine. In this post-hoc analysis, we assessed reliability, validity, responsiveness, and meaningful within-patient change from baseline to Month 3 for Work Productivity and Activity Impairment (WPAI) domain scores in patients with episodic migraine (EM) or chronic migraine (CM). Method The Phase 3, multicenter, randomized, double-blind, placebo-controlled CONQUER study (NCT03559257, N = 462) enrolled patients with EM or CM who failed two to four categories of prior preventive medication in past ten years. The analyses were performed for WPAI domain scores (absenteeism, presenteeism, overall work productivity, and non-work-related activity impairment). Migraine Specific Quality of Life Questionnaire version 2.1 (MSQv2.1) domain scores (Role Function-Restrictive [RFR] and Role Function-Preventive [RFP]), and monthly migraine headache days were used as anchors. Responder criteria were changes from baseline to Month 3 for each of these anchors and were defined as: increase in MSQ-RFR by ≥ 25.71 points and MSQ-RFP by ≥ 20.00 points and a 50% reduction in monthly migraine headache days. Assessments were performed for overall population, and patients with EM or CM. The meaningful change threshold was determined based on Youden index, Phi coefficient and sensitivity. Results Of 462 randomized patients, 444 who completed WPAI questionnaire were included in post-hoc analysis. Test-retest reliability over 3 months in a stable subgroup revealed moderate correlations for non-work-related Activity Impairment (ICC = 0.446) presenteeism (ICC = 0.438) and a fair correlation for overall work productivity loss (ICC = 0.360). At baseline, all correlations between WPAI domain scores and continuous anchor variables exceeded recommended threshold of ≥ 0.30, except for WPAI domain scores with number of monthly migraine headache days. Patients achieving pre-specified responsiveness thresholds for monthly migraine headache days, and MSQ-RFP, MSQ-RFR from baseline to Month 3 (responders) showed significant improvements in WPAI domain scores compared with non-responders (P < 0.001). The meaningful change thresholds of -20 (% unit) were identified for WPAI domain scores. Conclusion In conclusion, WPAI has sufficient validity, reliability, responsiveness, and appropriate interpretation standards to assess the impact of EM or CM on presenteeism and overall work productivity loss and non-work-related activity impairment. Trial registration NCT number of CONQUER study, NCT03559257.